Science Objectives for the Third Assessment - Education Commission of the States, Denver, CO. National Assessment of Educational Progress; Education Commission of the States, Denver, CO. National Assessment of Educational Progress ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
Presented is background information related to the third round of science assessment activities (1976-77) conducted by the National Assessment of Educational Progress (NAEP). Chapter one contains a description of the overall assessment plan, the general framework of objectives, criteria for selecting objectives, and procedures used for developing specific learner outcomes. Chapter two is focused on the cognitive domain while chapter three relates to attitudes, values, and experiences. Three appendices are included: (1) 1976-77 sample objectives, (2) a list of science consultants, and (3) objectives from cycles I and II. A short bibliography is included. (SA) Primary type of information provided by report: Assessment Instrument (Objectives); Procedures (Objectives Development).
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Contract Number: OEC-0-74-0506.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Affective Objectives; Cognitive Objectives; Educational Assessment; Elementary Secondary Education; Inquiry; Performance Criteria; Process Education; Science Education; Skill Development; Values; National Assessment of Educational Progress; Reports, Descriptive